Born green: Drivers and competencies of green entrepreneurship - Pimentel, P. (2022)
Sustainable development is one of the most prominent discussions of our times and promoting green new ventures can help reduce ecological footprints and meet the climate change goals. Despite its importance for the next decades, the study of green entrepreneurship (GE) is still very poor and being an emerging field of study can be considered still in its infancy. (Demirel et al, 2019; Sher et al, 2020). The current paper aims at providing a contribute to management science and business management practice by focusing on the research questions: (a) what are the most relevant theoretical frameworks researching drivers that trigger green entrepreneurial intention (GEI), and (b) what are the main theoretical frameworks investigating competencies that might favour or enhance the specific form of green entrepreneurial intention. Several theories have been developed to explain the classic entrepreneurial intention (EI) being the most noted the theory of planned behaviour (TPB) (Ajzen, 1991), and theory of entrepreneurial event (TEE) (Shapero and Sokol, 1982). A different stream of literature focus on individual competencies that can allow key issues to be captured and influence entrepreneurial intentions which are variable and can be acquired and learned over time (Mitchelmore and Rowley, 2010; Man et al, 2002). Nevertheless, these models do not contemplate on the role of the entrepreneurial intentions for a specific form like GE (Sher et al, 2020). We conducted a systematic literature review aiming at analysing quantitatively and qualitatively the relevant articles in indexed journals based on the PRISMA approach - Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Main findings are that recent relevant studies mainly adapt TPB to the determinants of GE by inserting new specific precedent variables. As to GE competencies, main authors depart from classic theoretical frameworks and finetune their approach to the more specific and broader dimensions of GE.